Effects of processing whole-plant corn silage on growth performance and nutrient digestibility in feedlot cattle - T.J. Wistuba; M.K. Siefers; J.E. Turner; G.L. Huck; K.K. Bolsen; Matthew A. Young; Ronald V. Pope (Kansas Agricultural Experiment Station Research Reports, 1998)
Sixty crossbred heifers and 12 crossbred steers were used to evaluate the effects of mechanically processing (crushing the kernels of) whole-plant corn silage on feedlot performance and nutrient digestibility. The three treatments were: preensiled processed, postensiled processed, and nonprocessed corn silages. Heifers fed the processed corn silages grew faster and were more efficient than those fed nonprocessed silage. Steers consuming the two processed silage rations had numerically higher DM, OM, NDF, and ADF digestibilities and significantly higher starch digestibilities than those fed the non- processed silage ration. These data suggest that processing whole-plant corn silage before or after ensiling has a positive effect on both rate and efficiency of gain and nutrient utilization, particularly when the kernels approach the black layer stage of maturity.
Keywords: Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 804; Cattlemen& #x27; s Day; 1998; Beef; Mechanically processed; Corn silage; Growing cattle; Feedlot